Security Inequalities in North America: Reassessing Regional Security Complex Theory - Richard Kilroy (Journal of Strategic Security, 2017)
This article re-evaluates earlier work done by the authors on Regional Security Complex Theory (RSCT) in North America, using sectoral analysis initially developed by Buzan and Waever, but also adding the variables of institutions, identity, and interests. These variables are assessed qualitatively in the contemporary context on how they currently impress upon the process of securitization within sectoral relations between Canada, Mexico, and the United States. The article reviews the movement from bilateral security relations between these states to the development of a trilateral response to regional security challenges post- 9/11. It further addresses the present period and what appears to be a security process derailed by recent political changes and security inequalities, heightened by the election of Donald Trump in 2016. The article argues that while these three states initially evinced a convergence of regional security interests after 9/11, which did create new institutional responses, under the current conditions, divergence in political interests and security inequalities have reduced the explanatory power of RSCT in North America. Relations between states in North American are becoming less characterized by the role of institutions and interests and more by identity politics in the region.